Meta-Analysis of the Effect of Psychotherapy in an Inpatient Setting: Examining the Moderating Role of Diagnosis and Therapeutic Approach. Issue 4 (2nd October 2022) - Cohen-Chazani, Yael; Lavidor, Michal; Gilboa-Schechtman, Eva; Roe, David; Hasson-Ohayon, Ilanit
Abstract : Objective: The current meta-analysis investigates the efficacy of psychotherapy during psychiatric hospitalization and examines the moderating role of diagnosis and therapeutic approach. Methods: We conducted systematic searches in literature databases, including PubMed, PsycInfo, and Google Scholar. In total, 37 samples were included for the meta-analysis with a total of 4, 443 patients. The primary outcome was the standardized mean differences in clinical status measured by symptomatic and functional measures. Results: The meta-analysis of 22 samples without a control group resulted in the upper end of the medium effect size for the overall effect of treatment during psychiatric hospitalization that included psychotherapy (k = 22, Cohen's d = 0.70, and 95% Cl 0.36 to 1.04). The meta-analysis of 15 samples with a control group resulted in the upper end of the low effect size for the contribution of psychotherapy to the improvement of patients' clinical status measured by symptomatic and functional measures (k = 15, Cohen's d = 0.43, and 95% CI 0.06 to 0.81). No significant effects were uncovered for psychotherapy orientation. Diagnosis was found to moderate the contribution of psychotherapy in an inpatient setting to the improvement of patients' clinical condition. Conclusion: Psychotherapy during psychiatric hospitalization may be an effective treatment. Across the various samples, psychotherapy has a moderate effect on the reduction of psychiatric symptoms beyond the overall effect of ward treatment.